A lethal chest injury following rhinoceros attack– a case report - Shah, S; Marharjan, N; Pradhan, SK; Kafle, P; Chapagain, D; Reddy, DJ (Journal of College of Medical Sciences-Nepal, 2012)
Injuries following wild animal encounters continue to be a major public health problem. Majority of such injuries are minor, however, many injuries remain undocumented. Many victim die, primarily in third-world countries, before receiving adequate medical care. Penetrating injuries to the chest following the attack by the wild animals, though rare, present a challenging problem. Though a great number of papers have been published regarding the injuries following encounter with animals, least are the lethal injuries occuring in the thoracic region and the survival out of these grave injury is very minimum. We herein present the least possible surviving case with lethal penetrating injury of the chest and left lung following the goring by the rhinoceros. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 52-55 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6827